Perovskite thin film based on functionalized aromatic amide micromolecules and preparation method and application thereof

By doping functional aromatic amide molecules into the perovskite precursor solution and preparing perovskite thin films using the gas quenching method, the problem of uneven halogen distribution in large-area perovskite thin films is solved, improving the efficiency and stability of the devices and making them suitable for industrial production.

CN120897650APending Publication Date: 2025-11-04SUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511029669.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-25
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Large-area perovskite thin films in photovoltaic cells suffer from performance degradation and accelerated phase separation due to uneven halogen distribution, affecting device efficiency and stability.

Method used

By doping functional aromatic amide molecules into a perovskite precursor solution, perovskite thin films are prepared using gas quenching and thermal annealing. These films are then deposited on a hole transport layer and combined with other layers of thin films to form an organic tandem solar cell.

Benefits of technology

It improves the crystallinity and uniformity of perovskite thin films, enhances the efficiency and stability of devices, makes it suitable for industrial production, and is applicable to wide-bandgap perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120897650A_ABST
    Figure CN120897650A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite thin film based on functionalized aromatic amide micromolecules and a preparation method and application thereof, and the preparation method comprises the steps: introducing the micromolecules into a perovskite precursor solution, replacing a traditional anti-solvent process with a mild and controllable gas quenching method, and achieving the preparation of a wide-band gap perovskite thin film with highly uniform initial distribution of a halogen phase. According to the technology, the separation rate of the bromine element is selectively delayed, the crystallization process is optimized, the crystallization quality of the thin film and the carrier transmission efficiency are remarkably improved, meanwhile, the problem of halogen phase segregation caused by ion migration can be inhibited through the continuous passivation effect of small molecules, and the device has high efficiency and long-term working stability. According to the process, harmful substance pollution and raw material waste are reduced, the homogeneous film forming characteristic can be expanded to the field of preparation of perovskite / organic laminated cells and large-area assemblies, and a new path is provided for development of efficient and stable photoelectric devices.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of photovoltaic materials, and particularly relates to a perovskite film based on a functionalized arylamide small molecule and a preparation method and application thereof. BACKGROUND

[0002] Perovskite / organic tandem solar cells have attracted much attention due to their breakthrough in overcoming the efficiency limit of single-junction cells and improving stability. Currently, the efficiency of small-area devices in the laboratory has exceeded 27%. However, there are still two major bottlenecks in scaling up to industrial size: one is the performance degradation caused by local property inhomogeneity, and the other is the accelerated degradation of phase separation under operating conditions. The initial composition uniformity of wide-bandgap perovskite films is the key to realizing large-area devices, especially the halogen distribution in complex component systems. Small-area devices can mask local defects through spatial averaging, but in large-area devices, component gradients can exacerbate bulk recombination, series resistance fluctuations, and sub-cell current mismatch, and can cause serious phase separation under light, high temperature, or bias, significantly reducing efficiency and stability. Compared with cations, the high mobility and low vacancy formation energy of halide ions (I- / Br-) lead to their easy stoichiometric deviation. Experiments show that nanoscale Br / I phases in large-area films can form micron-scale phase separation zones through defect-mediated migration, especially in wide-bandgap perovskites with high bromine content, bromide rapidly crystallizes to form dense defect zones, causing a sharp drop in local carrier lifetime. This process not only weakens the photocurrent and voltage of the front cell, but also destroys the overall efficiency and long-term stability of the tandem device through sub-cell mismatch. Current research focuses on precise control of halogen distribution, which needs to break through the limitations of traditional crystal orientation optimization and solvent coordination strategies, and develop film formation techniques suitable for large-area active layers. By inhibiting halogen migration paths and optimizing crystallization kinetics, it is expected to achieve the preparation of homogeneous films and promote the industrialization of tandem solar cells from the laboratory. SUMMARY

[0003] This section aims to summarize some aspects of the embodiments of the application and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract and title of the specification to avoid obscuring the purpose of this section, abstract and title, and such simplifications or omissions cannot be used to limit the scope of the application.

[0004] In view of the above and / or problems existing in the prior art, the present application is proposed.

[0005] Therefore, the purpose of the present application is to overcome the deficiencies in the prior art, and to provide a perovskite film based on a functionalized arylamide small molecule and a preparation method and application thereof.

[0006] To solve the above technical problems, the application provides a method for preparing an initial phase-uniform perovskite / organic laminated solar cell based on a functionalized arylamide small molecule, which comprises that a perovskite thin film based on the functionalized arylamide small molecule is prepared by spin coating of a FA 0.8 Cs 0.2 PbI 1.6 Br 1.4 The perovskite precursor solution is treated by a gas quenching method and then subjected to a heat annealing treatment to obtain the perovskite thin film.

[0007] The perovskite thin film based on the functionalized arylamide small molecule is deposited on a hole transport layer, and the hole transport layer comprises one or more of nickel oxide, polybis(4-phenyl)(2,4,6-trimethylphenyl)amine (PTAA), (2-(9H-carbazol-9-yl)ethyl)phosphonic acid (2PACz), [2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid, [2-(3,6-diphenyl-9H-carbazol-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethyl-9H-carbazol-9-yl)butyl]phosphonic acid, and [4-(7H-dibenzo[c,h]carbazol-7-yl)butyl]phosphonic acid. 0.8 Cs 0.2 PbI 1.6 Br 1.4 The solvent of the perovskite precursor solution is a mixed solution of N,N-dimethylformamide and methyl sulfoxide.

[0008] As a preferred scheme of the preparation method, the FA 0.8 Cs 0.2 PbI 1.6 Br 1.4 The doping concentration of the perovskite precursor solution is 0.3-1.0 mg / mL -1 ; the FA 0.8 Cs 0.2 PbI 1.6 Br 1.4 The concentration of the perovskite precursor solution is 1M.

[0009] As a preferred scheme of the preparation method, the gas quenching treatment condition is that the air gun is vertically placed at a distance of about 3-6 cm from the top of the substrate, the gas flow is introduced after 10-25 s of the start of the spin coating, the gas flow lasts for 10-20 s, and the gas flow pressure is about 20-40 psi; the heat annealing temperature is 80-150 DEG C, and the heat annealing time is 5-60 min.

[0010] Another object of the present application is to provide a perovskite thin film based on functionalized arylamide small molecules prepared by the preparation method, wherein the perovskite thin film based on functionalized arylamide small molecules has a thickness of 100-1000 nm.

[0011] Another object of the present application is to provide an application of a perovskite thin film based on functionalized arylamide small molecules in an organic laminated solar cell, wherein the preparation method of the organic laminated solar cell comprises sequentially preparing an electron transport layer 1, an ultrathin metal composite layer, a hole transport layer, an organic active layer, an electron transport layer 2, and an anode on the perovskite thin film.

[0012] As a preferred scheme of the application, the electron transport layer 1 comprises one or more of zinc oxide, PTAA, PBDB-T, PM6, PCBM, and C60@BCP, and tin oxide, and is prepared on the perovskite layer by a spin coating, vacuum evaporation or atomic layer deposition method, wherein the evaporation speed is 0.05-0.5 A / s. The electron transport layer 2 comprises one or more of PDINN, PNDIT-F3N, PDINO, and C60@BCP.

[0013] As a preferred scheme of the application, the ultrathin metal layer transport layer comprises Ag and Au, and is prepared on the electron transport layer by a vacuum evaporation method, wherein the evaporation speed is 0.05-0.5 A / s. The thickness is 0.5-2 nm.

[0014] As a preferred scheme of the application, the hole transport layer comprises one or more of MoO x 2PACz, MeO-2PACz, Ph-2PACz, and Me-4PACz, and is prepared by evaporation or spin coating, wherein the evaporation speed is 0.05-0.5 A / s. The spin coating speed is 1000-5000 rpm, the time is 10-60 s, and the thickness is 10-50 nm.

[0015] As a preferred scheme of the application, wherein: the organic active layer comprises PM6:Y6:PCBM, PM6:BTP-eC9:PCBM, PM6:BTP-eC9:D18, D18-Cl:N3:PCBM.

[0016] As a preferred scheme of the application, wherein: the anode is one of Au electrode, Ag electrode, Al electrode, Cu electrode, composite electrode, carbon electrode, PH1000 electrode, a metal electrode is prepared on the electron transport layer as the anode, and the metal electrode is prepared by vacuum evaporation, and the thickness is 10-200nm.

[0017] The application has the following beneficial effects:

[0018] (1) The application prepares a perovskite thin film with high crystalline quality on a transparent conductive substrate by doping a small molecule containing a functional aramid group into a perovskite precursor solution, and prepares a perovskite / organic stacked solar cell with high efficiency and good working stability based on the thin film.

[0019] (2) The method for preparing the perovskite thin film is also suitable for preparing a wide-bandgap perovskite solar cell, and the obtained wide-bandgap perovskite solar cell has high efficiency and good working stability.

[0020] (3) The application uses a more controllable gas quenching method to assist perovskite film formation, compared with the traditional anti-solvent film formation method, the method is more environmentally friendly and controllable, does not introduce an additional interface layer and post-processing technology, and the product performance is excellent, and is suitable for industrial production. BRIEF DESCRIPTION OF DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the embodiments of the application, the following will briefly introduce the drawings needed to be used in the embodiment description. Obviously, the drawings in the following description are only some embodiments of the application, and other drawings can also be obtained by those skilled in the art without any creative labor. Among them:

[0022] Figure 1 SEM surface morphology diagrams of perovskite thin films without doping and doped with functional aramid small molecules in the embodiments of the application;

[0023] Figure 2 XPS spectra of perovskite thin films without doping and doped with functional aramid small molecules in the embodiments of the application;

[0024] Figure 3 Peak position diagrams of PLmapping of perovskite thin films without doping and doped with functional aramid small molecules in the embodiments of the application before and after aging for 20 minutes under 3000mW cm-2 xenon lamp power.

[0025] Figure 4 Current-voltage curve of the wide bandgap perovskite solar cell of the embodiment of the present application (effective area 1.004 cm 2 );

[0026] Figure 5 Current-voltage curve of the wide bandgap perovskite solar cell doped with different concentrations of functional aramid small molecules of the embodiment of the present application (effective area 1.004 cm 2 );

[0027] Figure 6 Current-voltage curve of the perovskite / organic tandem solar cell of the embodiment of the present application (effective area 1.004 cm 2 );

[0028] Figure 7 Current-voltage curve of the perovskite / organic solar cell doped with different types of functional aramid small molecules of the embodiment of the present application (effective area 0.062 cm 2 );

[0029] Figure 8 Working stability curve of the wide bandgap perovskite solar cell without doping and doped with functional aramid small molecules of the embodiment of the present application;

[0030] Figure 9 Working stability curve of the perovskite / organic tandem solar cell without doping and doped with functional aramid small molecules of the embodiment of the present application.

[0031] Figure 10 Chemical structural formula of the functional aramid small molecule of the embodiment of the present application. DETAILED DESCRIPTION

[0032] In order to make the above objectives, features and advantages of the present application more apparent, the specific embodiments of the present application will be described in detail below with reference to the description of the embodiments.

[0033] In the following description, a lot of specific details are set forth in order to provide a thorough understanding of the present application, however, the present application can be practiced in other manners different from those described herein, and those skilled in the art can make similar generalizations without departing from the concept of the present application, therefore, the present application is not limited to the specific embodiments disclosed below.

[0034] Secondly, the "one embodiment" or "embodiment" referred to herein means that the specific features, structures or characteristics can be included in at least one implementation of the present application. The "in one embodiment" appearing in different places in the specification does not mean the same embodiment, nor is the embodiment alone or selectively mutually exclusive with other embodiments.

[0035] The raw materials used in the embodiments of the present application are all commercially available, and the ITO conductive glass and nickel oxide are purchased from Liaoning Optimal New Energy Technology Co., Ltd., 2PACz is purchased from TCI Co., Ltd., Japan, cesium iodide, iodomethanimine, lead iodide, lead bromide, C 60 , BCP is purchased from Xi'an Yurisheng Energy Technology Co., Ltd., MoO x , gold particles and silver particles are purchased from Hebei Qinbang New Material Technology Co., Ltd., PM6, D18 and BTP-eC9 are purchased from Shenzhen Yirong Photovoltaic Technology Co., Ltd., DMF, DMSO and chloroform are purchased from Beijing Bailingwei Technology Co., Ltd., 3-amino-5-fluorobenzamide is purchased from Shanghai McLean Biochemical Technology Co., Ltd., 3-amino-5-fluoro-2-methylbenzamide is purchased from Ambinter, France, 2-[(3-amino-5-fluorophenyl)formamidyl]acetamide and 3-amino-5-fluorobenzamide are purchased from Ambinter, France.

[0036] The device structure of the perovskite thin film solar cell based on the functionalized arylamide small molecule provided by the present application is: ITO conductive glass / hole transport layer 1 / perovskite active layer / electron transport layer 1 / ultra-thin metal composite layer / hole transport layer 2 / organic active layer / electron transport layer 2 / anode.

[0037] The hole transport layer 1 is NiO x , the electron transport layer 1 is C 60 @BCP, the ultra-thin metal composite layer is Au, and the hole transport layer is MoO x , the organic active layer is PM6:D18:BTP-eC9, the electron transport layer 2 is C 60 @BCP, and the anode is silver.

[0038] Preparation of the solution:

[0039] The hole transport layer NiO x : 10.0 mg of nickel oxide powder is weighed, 1 mL of deionized water is added and shaken, ultrasonic oscillation is performed for 5 min, and then filtration is performed for standby;

[0040] The hole transport layer [2-(9H-carbazol-9-yl)ethyl]phosphonic acid (2PACz): 1.2 mg of 2PACz powder is weighed, 4 mL of ethanol is added, and stirring is performed at 30℃ for 2 h, and then standby is performed;

[0041] Perovskite precursor solution: 147.5 mg PbI₂, 260.6 mg PbBr₂, 52.0 mg CsI, and 137.5 mg FAI were dissolved in 1 mL of a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) (volume ratio 4:1) to prepare a 1.0 M concentration of FAI. 0.8 Cs 0.2 PbI 1.6 Br 1.4 The solution was stirred at 60°C for 4 hours. Before use, the solution was filtered using a 0.45 mm PTFE organic filter head.

[0042] Organic active layer PM6:D18:BTP-eC9 solution: PM6, D18, and BTP-eC9 were prepared at a mass ratio of 0.8:0.2:1.2 to a total concentration of 14.96 mg / mL. -1 A chloroform (CF) solution was prepared, and 150% by mass of DIB was added as an additive. The mixture was stirred at 50°C for 4 hours and then left to stand.

[0043] Example 1

[0044] This embodiment provides a method for preparing perovskite thin films based on functionalized aromatic amide small molecules:

[0045] (1) First, prepare 0.5 mg mL -1 A perovskite solution doped with 3-amino-5-fluorobenzamide, the perovskite concentration being 1 M, and the selected perovskite composition being FA. 0.8 Cs 0.2 PbI 1.6 Br 1.4 The solvent used is a mixture of DMF and DMSO in a ratio of 4:1;

[0046] (2) Spin-coat a layer of NiO onto a clean ITO / FTO substrate. x A deionized aqueous dispersion of nickel oxide nanoparticles (concentration 15 mg / mL) was used. -1 The spin coating was performed at 3000 rpm, followed by annealing in air at 150°C for 30 min; then, a monomolecular self-assembled layer of 2PACz (concentration 0.3 mg / mL) was spin-coated once in a glove box. -1 Spin coating speed is 3000 rpm, annealing at 100℃ for 10 min;

[0047] (3) Spin-coat the prepared perovskite precursor solution onto the hole transport layer at a speed of 3000 rpm. Use a gentler and more controllable gas quenching method to assist in film formation. Place the air gun about 4 cm above the film. After spin coating for 10 seconds, start introducing nitrogen gas flow. The gas flow lasts for 15 seconds and the gas flow pressure is about 20 psi. Then immediately perform heat annealing to obtain the perovskite film. The heat treatment is annealing at 100°C for 30 min.

[0048] Comparative Example 1

[0049] A method for preparing perovskite thin films grown on a transparent conductive substrate:

[0050] (1) First, prepare a 1M perovskite solution. The selected perovskite component is FA. 0.8 Cs 0.2 PbI 1.6 Br 1.4 The solvent used is a mixture of DMF and DMSO in a ratio of 4:1;

[0051] (2) Spin-coat a layer of NiO onto a clean ITO / FTO substrate. x A deionized aqueous dispersion of nickel oxide nanoparticles (concentration 15 mg / mL) was used. -1 The spin coating was performed at 3000 rpm, followed by annealing in air at 150°C for 30 min; then, a monomolecular self-assembled layer 2PACz (concentration 0.3 mg / mL) was spin-coated in a glove box. -1 Spin coating speed is 3000 rpm, annealing at 100℃ for 10 min;

[0052] (3) Spin-coat the prepared perovskite precursor solution onto the hole transport layer at a speed of 3000 rpm. Use a gentler and more controllable gas quenching method to assist in film formation. Place the air gun about 4 cm above the film. After spin coating for 10 seconds, start introducing nitrogen gas flow. The gas flow lasts for 15 seconds and the gas flow pressure is about 20 psi. Then, perform heat annealing to obtain the perovskite thin film layer. The heat treatment is performed at 100°C for 15 min.

[0053] like Figure 1 The image shows planar SEM images of the doped and undoped perovskite films containing small aromatic amide molecules. As can be seen from the image, the doped perovskite grains are more uniform and dense, with increased grain size and a significantly reduced number of grain boundaries, in stark contrast to the small and irregular grains of the undoped film. Furthermore, the undoped initial film shows excessive lead iodide aggregation, which is significantly eliminated in the doped film, and the uniformity is greatly improved. Therefore, this invention improves the crystallinity quality of perovskite films, and the devices fabricated based on this method exhibit both high efficiency and good operational stability.

[0054] Example 2

[0055] The difference from Example 1 is that the substrate is replaced with a silicon wafer, otherwise it is the same as Example 1.

[0056] Comparative Example 2

[0057] The difference from Comparative Example 1 is that the substrate is replaced with a silicon wafer, otherwise it is the same as Example 1.

[0058] The prepared thin film was used for X-ray photoelectron spectroscopy, such as... Figure 2 The XPS spectra of undoped and doped perovskite films are shown. XPS results indicate that the doped aramid molecules remain in the film after heat treatment annealing and can interact with bromine and iodine in the perovskite, with a stronger interaction with bromine than with iodine. Simultaneously, the carbonyl group in the molecule can coordinate with uncoordinated lead in the perovskite, passivating defects and thus suppressing phase separation.

[0059] Example 3

[0060] The difference from Example 1 is that the substrate is replaced with high-transmittance glass, otherwise it is the same as Example 1.

[0061] Comparative Example 3

[0062] The difference from Comparative Example 1 is that the substrate is replaced with high-transmittance glass, otherwise it is the same as Example 1.

[0063] The prepared thin film was used for photoluminescence spectral imaging tests, such as... Figure 3 As shown, Figure 3 For undoped and doped perovskite films with small aromatic amide molecules under initial conditions and 3000 mW cm⁻¹ -2 After 20 minutes of photoaging, the PL emission peak positions of the perovskite thin films were analyzed. The results showed that the PL emission peak positions in the region of the film doped with aromatic amide molecules were essentially the same after heat treatment annealing, demonstrating the extremely high homogeneity of the initial film. In contrast, the undoped film clearly showed an iodine-rich phase (bright yellow region), with inconsistent emission peak positions within this region, indicating heterogeneity in halogen distribution. After aging, the homogeneity of the undoped film further decreased, and severe phase separation occurred, indicating that phase separation is more severe in films with initially heterogeneous phase distribution after aging. The doped film, benefiting from its superior initial phase homogeneity, maintained essentially unchanged peak positions after aging, demonstrating that the doping of aromatic amide molecules significantly improved the initial phase homogeneity of the film and suppressed phase separation under operating conditions.

[0064] Example 4

[0065] (1) First, a perovskite solution doped with 0.5 mg / mL 3-amino-5-fluorobenzamide was prepared. The concentration of the perovskite was 1 M, and the selected perovskite component was FA. 0.8 Cs 0.2 PbI 1.6 B r1.4 The solvent used is a mixture of DMF and DMSO in a ratio of 4:1.

[0066] (2) In a clean 1.9×1.9cm 2 A layer of NiO is spin-coated onto ITO / FTO. x A deionized aqueous dispersion of nickel oxide nanoparticles (concentration 15 mg / mL) was spin-coated at 3000 rpm and annealed in air at 150 °C for 30 min. Then, a monomolecular self-assembled layer 2PACz (concentration 0.3 mg / mL) was spin-coated once in a glove box at 3000 rpm and annealed at 100 °C for 10 min.

[0067] (3) Spin-coat the prepared perovskite precursor solution onto the hole transport layer at a speed of 3000 rpm. Use a gentler and more controllable gas quenching method to assist in film formation. Place the air gun about 4 cm above the film. After spin coating for 10 seconds, start introducing nitrogen gas flow. The gas flow lasts for 15 seconds and the gas flow pressure is about 20 psi. Then, perform heat annealing to obtain the perovskite thin film layer. The heat treatment is performed at 100°C for 15 min.

[0068] (4) Place the thin film in a vacuum coating machine to deposit the electron transport layer C. 60 BCP, vapor deposition C 60 The rate is With a thickness of 20 nm, the rate of BCP deposition is... Thickness is 6nm;

[0069] (5) The thin film was placed in a vacuum coating machine to deposit a gold electrode with a thickness of 100 nm. The electrode was made of metallic Ag, and the final effective area was 1.004 cm². 2 Wide-bandgap perovskite solar cells doped with functional aromatic amide molecules.

[0070] Comparative Example 4

[0071] (1) First, a 1M perovskite precursor solution was prepared. The selected perovskite component was FA. 0.8 Cs 0.2 PbI 1.6 Br 1.4 The solvent used is a mixture of DMF and DMSO in a ratio of 4:1.

[0072] (2) In a clean 1.9×1.9cm2 A layer of NiO is spin-coated onto ITO / FTO. x A deionized aqueous dispersion of nickel oxide nanoparticles (concentration 15 mg / mL) was spin-coated at 3000 rpm and annealed in air at 150 °C for 30 min. Then, a monomolecular self-assembled layer 2PACz (concentration 0.3 mg / mL) was spin-coated once in a glove box at 3000 rpm and annealed at 100 °C for 10 min.

[0073] (3) Spin-coat the prepared perovskite precursor solution onto the hole transport layer at a speed of 3000 rpm. Use a gentler and more controllable gas quenching method to assist in film formation. Place the air gun about 4 cm above the film. After spin coating for 10 seconds, start introducing nitrogen gas flow. The gas flow lasts for 15 seconds and the gas flow pressure is about 20 psi. Then, perform heat annealing to obtain the perovskite thin film layer. The heat treatment is performed at 100°C for 15 min.

[0074] (4) Place the thin film in a vacuum coating machine to deposit the electron transport layer C. 60 BCP, vapor deposition C 60 The rate is With a thickness of 20 nm, the rate of BCP deposition is... Thickness is 6nm;

[0075] (5) The thin film was placed in a vacuum coating machine to deposit gold electrodes with a thickness of 100 nm. The electrodes were made of metal Ag, and finally a perovskite solar cell with an effective area of ​​0.062 cm2 was obtained.

[0076] Comparing the performance of the perovskite solar cells in Example 4, we obtain Figure 4 Current-voltage curve of perovskite solar cell (effective area 1.004 cm²) 2 (See Table 1) and the light intensity is AM1.5G 100mW cm⁻¹ -2 .

[0077] Table 1 Comparison of photovoltaic performance parameters of wide-bandgap perovskite solar cells

[0078]

[0079] from Figure 4 As shown in Table 1, doping the perovskite bulk with functional aromatic amide molecules significantly improves the open-circuit voltage and fill factor of the device, achieving a device efficiency of 18.61% (effective area 1.004 cm²). 2Compared to undoped perovskite, the voltage was increased by 0.039V and the fill power was improved by 3.43%. The study shows that doping simple functional aromatic amide molecules into the precursor solution and preparing perovskite films using a milder and more environmentally friendly gas quenching method results in perovskite films with high crystallinity, large grain size, and low defect density, thereby promoting charge transport and reducing non-radiative recombination. The PCE of undoped perovskite devices differed by 1.5% compared to doped devices, demonstrating the unique advantages of doping with functional aromatic amide molecules.

[0080] Example 5

[0081] The difference from Example 4 is that in step (1), 0.3 mg mL was prepared. -1 A perovskite solution containing 3-amino-5-fluorobenzamide was prepared. The final yield had an effective surface area of ​​1.004 cm². 2 Wide-bandgap perovskite solar cells doped with 3-amino-5-fluorobenzamide.

[0082] Example 6

[0083] The difference from Example 4 is that step (1) prepared 1.0 mg mL -1 A perovskite solution containing 3-amino-5-fluorobenzamide was prepared. The final yield had an effective surface area of ​​1.004 cm². 2 Wide-bandgap perovskite solar cells doped with 3-amino-5-fluorobenzamide.

[0084] Comparing the performance of the perovskite solar cells in Examples 4-6, we obtain Figure 5 Current-voltage curves of perovskite / organic tandem solar cells doped with different types of functional aromatic amide molecules (effective area 1.004 cm²) 2 (See Table 2) and the light intensity is AM1.5G 100mW cm⁻¹. -2 .

[0085] Table 2 Comparison of photovoltaic performance parameters of wide-bandgap perovskite solar cells doped with different concentrations of 3-amino-5-fluorobenzamide

[0086]

[0087] from Figure 5 As shown in Table 2, the doping of functional aromatic amide small molecules into the perovskite matrix at concentrations of 0.3–1.0 mg / mL... -1 Within the specified range, the device performance is high, demonstrating that the material has a wide doping concentration window. Furthermore, at 0.5 mg / mL... -1 Optimal doping concentration.

[0088] Example 7

[0089] (1) In step (4) of Example 4, the electron transport layer C is deposited in a vacuum coating machine. 60 The BCP film was placed in a vacuum deposition machine to deposit an ultrathin metal layer of Au. The Au deposition rate was... Thickness is 1 nm;

[0090] (2) Place the thin film in a vacuum coating machine to vapor deposit a hole transport layer, MoO. x MoO vapor deposition x The rate is The thickness is 11nm;

[0091] (3) Spin-coat a self-assembled monolayer 2PACz with a concentration of 0.3 mg / mL onto the above film. -1 Spin coating speed is 3000 rpm, annealing at 100℃ for 10 min;

[0092] (4) An organic active layer was spin-coated onto the monolayer. The selected organic active layer system was PM6:D18:BTP-eC9, and the donor concentration was 15 mg / mL. -1 The active layer film was spin-coated onto the hole transport layer in the composite interconnect layer at a speed of 2500 rpm to obtain an active layer film with a thickness of about 120 nm.

[0093] (5) Place the thin film in a vacuum coating machine to evaporate the electron transport layer C. 60 BCP, vapor deposition C 60 The rate is With a thickness of 10 nm, the rate of BCP deposition is: Thickness is 6nm;

[0094] (6) The thin film was placed in a vacuum coating machine to deposit a gold electrode with a thickness of 100 nm. The electrode was made of metallic Ag, and the final effective area was 1.004 cm². 2 Perovskite / organic tandem solar cells doped with small aromatic amide molecules.

[0095] Comparative Example 7

[0096] (1) In step (4) of Comparative Example 4, the electroplated transport layer C is deposited in a vacuum coating machine. 60 The BCP film was placed in a vacuum deposition machine to deposit an ultrathin metal layer of Au. The Au deposition rate was... Thickness is 1 nm;

[0097] (2) Place the thin film in a vacuum coating machine to vapor deposit a hole transport layer, MoO. x MoO vapor deposition x The rate is The thickness is 11nm;

[0098] (3) A monomolecular self-assembled layer 2PACz with a concentration of 0.3 mg / mL was spin-coated onto the above film. -1 Spin coating speed is 3000 rpm, annealing at 100℃ for 10 min;

[0099] (4) An organic active layer was spin-coated onto the monolayer. The selected organic active layer system was PM6:D18:BTP-eC9, and the donor concentration was 15 mg / mL. -1 The active layer film was spin-coated onto the electron transport layer in the composite interconnect layer at a speed of 2500 rpm to obtain an active layer film with a thickness of about 120 nm.

[0100] (5) Place the thin film in a vacuum coating machine to evaporate the electron transport layer C. 60 BCP, vapor deposition C 60 The rate is With a thickness of 10 nm, the rate of BCP deposition is: Thickness is 6nm;

[0101] (6) The thin film was placed in a vacuum coating machine to deposit a gold electrode with a thickness of 100 nm. The electrode was made of metallic Ag, and the final effective area was 1.004 cm². 2 Perovskite / organic tandem solar cells.

[0102] Comparing the performance of the perovskite solar cells in Example 5, we obtain Figure 6 Current-voltage curves of perovskite / organic tandem solar cells (effective area 1.004 cm²) 2 (See Table 3) and the light intensity is AM1.5G 100mW cm⁻¹. -2 .

[0103] Table 3 Comparison of photovoltaic performance parameters of perovskite / organic tandem solar cells

[0104]

[0105] from Figure 6 As shown in Table 3, doping the perovskite precursor solution with functional aromatic amide small molecules significantly improves the open-circuit voltage and fill factor of the prepared multilayer device, achieving a device efficiency of 25.21% (effective area of ​​1.004 cm²). 2Compared to undoped perovskite, the voltage was increased by 0.04V and the fill power was improved by 5.87%. The study shows that doping simple aromatic amide molecules into the precursor solution and preparing perovskite films using a milder and more environmentally friendly gas quenching method results in perovskite films with high crystallinity, large grain size, and low defect density. This reduces non-radiative recombination, promotes balanced recombination in the intermediate recombination layer, and improves the open-circuit voltage of the stacked device. The PCE of the undoped perovskite device differed by 3.4% compared to the doped one, demonstrating the unique advantages of doped functional aromatic amide molecules.

[0106] Example 8

[0107] (1) Prepare a solution containing 0.5 mg of [unspecified substance] mL -1 A perovskite solution containing 3-amino-5-fluorobenzamide, with a perovskite concentration of 1 M, and the selected perovskite component being FA. 0.8 Cs 0.2 PbI 1.6 Br 1.4 The solvent used is a mixture of DMF and DMSO in a ratio of 4:1.

[0108] (2) The difference from Example 7 is that the substrate in step (2) is replaced with a 1.5 × 1.5 cm substrate. 2 High-transparency conductive glass. The final effective area is 0.062 cm². 2 Perovskite / organic tandem solar cells doped with 3-amino-5-fluorobenzamide.

[0109] Comparative Example 8

[0110] (1) The difference from Comparative Example 7 is that the substrate in step (2) is replaced with a 1.5 × 1.5 cm substrate. 2 High-transparency conductive glass. The final effective area is 0.062 cm². 2 Perovskite / organic tandem solar cells.

[0111] Example 9

[0112] The difference from Example 6 is that 3-amino-5-fluorobenzamide in step (1) is replaced with 3-amino-5-fluoro-2-methylbenzamide, otherwise it is the same as Example 6.

[0113] Example 10

[0114] The difference from Example 6 is that 3-amino-5-fluorobenzamide in step (1) is replaced with 2-[(3-amino-5-fluorophenyl)formamido]acetamide, otherwise it is the same as Example 6.

[0115] Comparing the performance of perovskite solar cells in Examples 8-10 with that in Comparative Example 8, the following results were obtained.Figure 7 Current-voltage curves of perovskite / organic tandem solar cells doped with different types of functional aromatic amide molecules (effective area 0.062 cm²). 2 (See Table 4) and the light intensity is AM1.5G 100mW cm⁻¹ -2 .

[0116] Table 4 Comparison of photovoltaic performance parameters of perovskite / organic tandem solar cells doped with different types of functional aromatic amide small molecules

[0117]

[0118] from Figure 8 As shown in Table 4, doping different types of functional aromatic amide small molecules into the perovskite matrix significantly improved the open-circuit voltage and fill factor of the prepared multilayer devices. After doping with 3-amino-5-fluoro-2-methylbenzamide, 2-[(3-amino-5-fluorophenyl)carbamate]acetamide, and 3-amino-5-fluorobenzamide, respectively, the voltage increased by approximately 0.04 V compared to undoped calcium, with efficiencies reaching 25.70%, 25.80%, and 25.96%, respectively. The study indicates that doping different types of functional aromatic amide small molecule salts into the precursor solution and preparing perovskite films using a milder and more environmentally friendly gas quenching method results in perovskite films with higher crystallinity, larger grain size, and lower defect density, thereby promoting charge transport and reducing non-radiative recombination. The PCE of the undoped perovskite device was only 24.60%, demonstrating the unique advantages of doping with functional aromatic amide small molecules.

[0119] To evaluate the operational stability of the devices, stability tests were conducted. The perovskite solar cell is shown in Example 4, and the perovskite / organic tandem solar cell is shown in Example 5.

[0120] The prepared perovskite solar cells were placed in a nitrogen atmosphere at 25°C to test their operational stability. Figure 8 The figure shows the operational stability curves of perovskite solar cells doped with functional aromatic amide molecules and those without. As shown, the undoped perovskite solar cell retains only 75% of its initial efficiency after 900 hours of operation, indicating that ion migration occurs in the undoped device under prolonged operating conditions, causing phase segregation in the perovskite active layer and thus affecting device stability. In contrast, the perovskite solar cell doped with functional aromatic amide molecules retains 87% of its initial efficiency after 1800 hours. This demonstrates that doping with functional aromatic amide molecules effectively suppresses ion migration within the perovskite film, improving the stability of the perovskite thin film and resulting in perovskite devices with excellent operational stability.

[0121] The prepared perovskite / organic tandem solar cells were placed in a nitrogen atmosphere at 25°C to test their operational stability. Figure 9 The figure shows the operational stability curves of perovskite / organic tandem solar cells doped with functional aromatic amide molecules and undoped cells. As shown, the undoped perovskite solar cell retains only 75% of its initial efficiency after 900 hours of operation. This indicates that under prolonged operating conditions, ion migration occurs in the undoped device, causing phase segregation in the perovskite active layer. Furthermore, I- migration disrupts the ultrathin metal composite layer in the interconnect layer, severely affecting internal carrier recombination and consequently impacting the stability of the tandem device. In contrast, the perovskite solar cell doped with functional aromatic amide molecules retains 90% of its initial efficiency after 1600 hours. This demonstrates that doping with functional aromatic amide molecules can prepare a film with a uniform initial phase, effectively suppressing ion migration within the perovskite layer, improving the stability of the perovskite film, and protecting the ultrathin metal layer of the interconnect layer. The resulting perovskite / organic tandem device exhibits excellent operational stability. Figure 10 The chemical structural formula of the functional aromatic amide small molecule is shown in the embodiment of the present invention.

[0122] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the present invention.

Claims

1. A method for preparing perovskite thin films based on functionalized aromatic amide small molecules, characterized in that: The perovskite thin film based on functionalized aromatic amide small molecules was spin-coated with FA small molecules containing functionalized aromatic amide groups. 0.8 Cs 0.2 PbI 1.6 Br 1.4 The perovskite precursor solution was obtained by gas quenching followed by hot annealing. The perovskite film based on functionalized aromatic amide small molecules is deposited on the hole transport layer, which includes one or more of the following: nickel oxide, poly(4-phenyl)(2,4,6-trimethylphenyl)amine (PTAA), (2-(9H-carbazole-9-yl)ethyl)phosphonic acid (2PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [2-(3,6-diphenyl-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, and [4-(7H-dibenzocarbazole-7-yl)butyl]phosphonic acid. The small molecules with aromatic amide groups include one or more of 3-amino-5-fluorobenzamide, 3-amino-4,5-difluorobenzamide, 2,3-diamino-4,5-difluorobenzamide, 3-amino-5-fluoro-2-methylbenzamide, 3-amino-5-fluoro-4-methylbenzamide, 3-amino-5-fluoro-N-methylbenzamide, 2-[(3-amino-5-fluorophenyl)carbamoyl]acetamide, and 3-amino-5-fluoro-N-(2,2,2-trifluoroethyl)benzamide; The FA 0.8 Cs 0.2 PbI 1.6 Br 1.4 The solvent for the perovskite precursor solution is a mixture of N,N-dimethylformamide and methyl sulfoxide.

2. The preparation method according to claim 1, characterized in that: The FA doped with small molecules containing functional aromatic amide groups 0.8 Cs 0.2 PbI 1.6 Br 1.4 The doping concentration of the perovskite precursor solution is 0.3–1.0 mg / mL. -1 ; FA 0.8 Cs 0.2 PbI 1.6 Br 1.4 The concentration of the perovskite precursor solution is 0.4–2 M.

3. The preparation method according to claim 1, characterized in that: The gas quenching conditions are as follows: the air gun is placed vertically about 3 to 6 cm away from the top of the substrate; 10 to 25 seconds after the spin coating begins, the airflow is introduced and continues for 10 to 20 seconds; the gas flow pressure is about 20 to 40 psi; the temperature of the heat annealing is 80 to 150°C and the heat annealing time is 5 to 60 minutes.

4. The perovskite thin film based on functionalized aromatic amide small molecules prepared by the preparation method according to claims 1 to 3, characterized in that: The thickness of the perovskite film based on functionalized aromatic amide small molecules is 100–1000 nm.

5. The application of the perovskite thin film based on functionalized aromatic amide small molecules as described in claim 4 in organic tandem solar cells, characterized in that: The method for preparing the organic tandem solar cell includes sequentially preparing an electron transport layer 1, an ultrathin metal composite layer, a hole transport layer, an organic active layer, an electron transport layer 2, and an anode on a perovskite thin film.

6. The application as described in claim 5, characterized in that: The electron transport layer 1 includes zinc oxide, PTAA, PBDB-T, PM6, PCBM, and C. 60 An electron transport layer is prepared on a perovskite layer using one or more of BCP and tin oxide, employing spin coating, vacuum evaporation, or atomic layer deposition methods, wherein the evaporation rate is [missing information]. The thickness is 10–50 nm; the electron transport layer 2 includes PDINN, PNDIT-F3N, PDINO, and C. 60 One or more of @BCP.

7. The application as described in claim 4, characterized in that: The ultrathin metal transport layer comprises Ag and Au; it is prepared on the electron transport layer using a vacuum evaporation method, wherein the evaporation rate is [missing information]. The thickness is 0.5–2 nm.

8. The application as described in claim 4, characterized in that: The hole transport layer includes MoO x One or more of 2PACz, MeO-2PACz, Ph-2PACz, and Me-4PACz are selected; the mixture is prepared by vapor deposition or spin coating, wherein the vapor deposition rate is [missing information]. The spin coating speed is 1000-5000 rpm, the time is 10-60 s, and the thickness is 10-50 nm.

9. The application as described in claim 4, characterized in that: The organic active layer includes PM6:Y6:PCBM, PM6:BTP-eC9:PCBM, PM6:BTP-eC9:D18, and D18-Cl:N3:PCBM.

10. The application as described in claim 4, characterized in that: The anode is one of Au electrode, Ag electrode, Al electrode, Cu electrode, composite electrode, carbon electrode, or PH1000 electrode. A metal electrode is prepared on the electron transport layer as the anode and prepared by vacuum evaporation, with a thickness of 10-200 nm.